2020
DOI: 10.3390/bs10090140
|View full text |Cite
|
Sign up to set email alerts
|

A Time-Lagged Examination of the Greenhaus and Allen Work-Family Balance Model

Abstract: The work-family interface is a compelling topic that calls into question labor market dynamics and work processes, together with important social and family composition changes. The present study aimed at examining the antecedents of Work-Family Balance (WFB) in Italy consistent with Greenhaus and Allen’s (2011) conceptual model in which the characteristics of work and family roles have an indirect impact on work-family balance through Work-Family Conflict (WFC) and Work-Family Enrichment (WFE), and where job … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 73 publications
1
24
1
Order By: Relevance
“…Several studies have shown that the simultaneous participation in family and work roles generates stress in an individual's life [8] and these conflicting situations may also negatively affect the person's health and well-being [32]. Managing the boundaries of work and family roles is important for a person's life [33] and the lack of balance between work and family roles can lead to negative outcomes.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have shown that the simultaneous participation in family and work roles generates stress in an individual's life [8] and these conflicting situations may also negatively affect the person's health and well-being [32]. Managing the boundaries of work and family roles is important for a person's life [33] and the lack of balance between work and family roles can lead to negative outcomes.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Job demands and resources play an important role as antecedents in the relationship between work and family domains [8]. On one side, job demands (i.e., workload) can lead to a deterioration of both physiological and psychological health as they require a psycho-physical effort; on the other side, job resources (i.e., job control, coworkers, and supervisor support) facilitate the achievement of work objectives and stimulate growth, learning, and personal development [41].…”
Section: Work-related Resources and Demandsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the relationship between work and life combines the compatibility and conflict between work and family life and integrates perspectives of conflict and balance (Frone et al, 2003 ). Evidence suggests that work-life balance and conflict are related but are affected by different factors (Landolfi et al, 2020 ). Work–family conflict occurs when a woman experiences incompatible demands between her work and family roles, making it difficult to participate in both roles.…”
Section: Literature Reviewmentioning
confidence: 99%